Local rules - Brandon, Jay (New York : Pocket Books, 1995)
After receiving a speeding ticket, former assistant D.A. Jordan Marshall's punishment is to serve as the defender for a local boy being railroaded on a murder charge.
Keywords: Texas -- Fiction; Detective and mystery fiction